Effects of initial treatment on the dynamics of renal functional reserve in stage-I hypertensive patients - Lyudmila Khimion; Lilia Tymoshchuk; Mariia Rybytska (National Scientific Medical Center, 2018)
Objective: To determine the functional state of the kidneys in patients with the I stage essential hypertension with different total risk of cardiovascular complications and to assess the effect of early medication (angiotensin II receptor blocker) on the dynamics of changes in the functional renal reserve. Material and Methods: This study included 80 patients with the established diagnosis - the I stage essential hypertension of the I-III grade in age from 18 to 60 years (28 women (35 %), the average age is 40,1 (35,0-56,0) years; men - 57 (71%), average age - 40,2 (37,0-53,0) years. A risk factor count was used to assess the overall risk of cardiovascular complications in hypertension. Functional renal reserve and endothelium-independent vasodilation of the brachial artery were defined. Statistical analysis was performed using SPSS Statistics. Results: In patients with high risk, the depleted and decreased functional renal reserve was most often detected, which was 55% of patients. It is also important to note that patients with even a low risk of cardiovascular complications have already had renal damage as a reduced or depleted functional renal reserve. Patients with a low risk of cardiovascular complications who had not started drug treatment on their first visit had a 2.3-fold (95% CI 1,048-4,896) higher relative risk of developing kidney damage in comparison with patients who had started medication therapy without delay. Conclusion: Diagnosis of functional renal reserve in patients with a low risk of developing cardiovascular complications in stage I arterial hypertension is an important component for predicting the further development of kidney damage and timely prevention of its progression. The early onset of drug treatment reduces the relative risk of developing kidney damage by 2.3 times in patients with arterial hypertension.